Change in patterns of HIV status disclosure in the HAART era and association of HIV status disclosure with depression level among women. Issue 9 (2nd September 2017) - Liu, Chenglong; Goparaju, Lakshmi; Barnett, Andrew; Wang, Cuiwei; Poppen, Paul; Young, Mary; Zea, Maria Cecilia
ABSTRACT: Whether widespread use of HAART changed patterns of HIV status disclosure among women living with HIV is largely unknown. In addition, the association between time to first HIV disclosure and depression has not been fully explored among women. A retrospective cross-sectional survey was conducted among HIV-infected women from the Washington, DC site of the Women's Interagency HIV Study to collect detailed information about their HIV status disclosure behavior. A sample of 202 HIV-positive women, 102 diagnosed prior to and 100 post-HAART era participated in this study. Relationships between treatment era when diagnosed (pre-HAART or HAART era) and patterns of HIV status disclosure, and associations between HIV status disclosure and depression level were examined using generalized linear regression models with generalized estimating equation to adjust for repeated measurements from the same individuals. Our analyses showed that treatment era was not associated with either comfort level of HIV status disclosure or time to first HIV disclosure to either family members or friends. However, women were less likely to disclose HIV status to their family members in the HAART era ( P  = 0.006) after adjusting for social network type, comfort level of disclosure, time to first disclosure and length of follow-up time. In addition, longer time to first HIV disclosure, but not comfort level or extent of HIV status disclosure, was independently associated with depression levels as measured by CES-D score at study enrollment ("a few months after" vs "within a few days": P  = 0.008). More definitive studies utilizing longitudinal designs should be conducted to further examine impact of HAART era on HIV status disclosure and effect of HIV status disclosure on mental health.